Acute kidney injury and maladaptive tubular repair leading to renal fibrosis. Issue 3 (May 2020) - Yu, Samuel M.-W.; Bonventre, Joseph V.
Abstract : Purpose of review: Despite improvements in acute kidney injury (AKI) detection, therapeutic options to halt the progression of AKI to chronic kidney disease (CKD) remain limited. In this review, we focus on recent discoveries related to the pathophysiology of the AKI to CKD continuum, particularly involving the renal tubular epithelial cells, and also discuss related ongoing clinical trials. While our focus is on injured renal tubular epithelial cells as initiators of the cascade of events resulting in paracrine effects on other cells of the kidney, the summation of maladaptive responses from various kidney cell types ultimately leads to fibrosis and dysfunction characteristic of CKD. Recent findings: Recent findings that we will focus on include, but are not limited to, characterizations of: the association between cell cycle arrest and cellular senescence in renal tubular epithelial cells and its contribution to renal fibrosis, chronic inflammation with persistent cytokine production and lymphocyte infiltration among unrepaired renal tubules, mitochondrial dysfunction and a unique role of cytosolic mitochondria DNA in fibrogenesis, prolyl hydroxylase domain proteins as potential therapeutic targets, and novel mechanisms involving the Hippo/yes-associated protein/transcriptional coactivator with PDZ-binding pathway. Summary: Potential therapeutic options to address CKD progression will be informed by a better understanding of fibrogenic pathways. Recent advances suggest additional drug targets in the various pathways leading to fibrosis.